Living Donor Liver Transplantation for Hepatocellular Carcinoma: Appraisal of the United Network for Organ Sharing Modified TNM Staging - Bhatti, Abu Bakar Hafeez; Waheed, Anum; Khan, Nasir Ayub (Frontiers in Surgery, 2021)
Background: In deceased donor liver transplantation (DDLT), transplant eligibility for T3-T4 HCC requires successful down staging (DS). Living donor liver transplantation (LDLT) can be considered selectively in these patients without DS , but its role is not defined. The objective of the current study was to assess outcomes of LDLT for HCC based on UNOS staging with no prior DS. Materials and methods: Patients who underwent LDLT for HCC (n=262) were staged based on modified UNOS TNM staging. High risk factors were identified and 5 year recurrence free survival was compared in patients with T2-T4 HCC. Results: Median follow up was 30.2(16.4-46.3) months. Recurrence rate in T1, T2 ,T3, T4a and T4b HCC was 0, 10.1%, 16.1%, 5.9% and 37.5% (P=0.01) respectively. On multivariate analysis, AFP > 600 ng/ml[ HR:11.7, P<0.001] and T4b HCC (macrovascular invasion) [HR=5.6, P=0.03] were predictors of recurrence. After exclusion of AFP > 600 ng/ml, 5 year RFS for T2, T3 and T4a HCC was 94%, 86% and 92% (P=0.1). Rate of microvascular invasion between T2 and T3 HCC was 24.3% vs 53.6% (P=0.005) and between T2 and T4a HCC was 24.3% vs 36.7%(P=0.2). Overall, twenty six (19.4%) patients were over staged and 23 (17.1%) were under staged on preoperative imaging. The 5 year RFS in patients with identical preoperative and histopathological staging was 94%, 87% and 94% (P=0.6). Conclusion: LDLT without prior DS leads to comparable survival for UNOS T2, T3 and T4a HCC, as long as AFP is < 600 ng/ml.